OPTIMIZATION OF DEVELOPMENT PERFORMANCEANDQUALITY IMPROVEMENT OF BIODIESEL FROM OIL FRACTIONOF LIQUID WASTE OF PALM OIL PROCESS BY USING ULTRASONIC WAVES - Budiyanto, Hasan Basri Daulay dan Anita Fandra Aldiona (Jurnal Teknologi Industri Pertanian, 2012)
ABSTRACT The objectives of the study were to evaluate the quantity and quality of biodiesel produced via conventional and ultrasonic methods using various acid catalysts; and to determine the most efficient methods in producing a good quality of biodiesel. Oil fraction from palm oil mill effluent (POME) was used. During esterification process, three variation of acid catalyst and two different reaction conditions were used. The result indicates that the use of mix 0.5% BF3 and 0.5% H2SO4  could yield biodiesel more than the other method. Similarly, the quality of biodiesel produced  complied with SNI No. as-782-2006, especially for the parameters of specific  gravity, viscosity, cetane number, iodine number, and acid value. Keywords: methyl ester, ultra sonic, ASTM, oil fraction of POME